A concise review of the brown macroalga Ascophyllum nodosum (Linnaeus) Le Jolis - Pereira, Leonel; Morrison, Liam; Shukla, Pushp Sheel; Critchley, Alan T. (Journal of applied phycology, 2020)
Ascophyllum nodosum is a large and common brown alga. The fronds are olive-brown but can appear yellowish when stressed. It is a common, intertidal species around the periphery of the North Atlantic Ocean. It is particularly common on the north-western coast of Europe (from Svalbard to Portugal), including east Greenland, Iceland and the NE coast of N America (from New York to Newfoundland). This intertidal fucoid has long fronds with large egg-shaped airbladders. The fronds can reach 2 m (extremes of 5–7 m) in length. Depending on nutrient availability, the fronds are yellow, and at low tide, they can form extensive beds appearing to be monospecific to the casual observer. This seaweed is long lived and can be a dominant, climax community species of the middle shore. Ascophyllum nodosum is very effective at accumulating nutrients and minerals from the surrounding seawater. Due to the presence of many bioactive components, its harvested biomass is a valuable resource for human enterprise. This species is exploited for use in products such as food, fertiliser, soil conditioners, biostimulants (for phyco-elicitors), animal feed, skin and hair care products, cleaners, de-greasers, equestrian products and nutritional supplements. It is also a popular ingredient in cosmetology and thalassotherapy.